The Patient Protection and Affordable Care Act and Utilization of Preventive Health Care Services - Victor Eno; Senthilkumar Mehalingam; Thomas I. Nathaniel (SAGE Open, 2016)
We examined how (a) health insurance coverage, and (b) familiarity with the Patient Protection and Affordable Care Act (ACA)’s or ObamaCare mandate of cost-free access to preventive health services, affect the use of preventive services by residents of a minority community. It was based on primary data collected from a survey conducted during March to April 2012 among a sample of self-identified African American adults in Tallahassee-Leon County area of northwest Florida. The Statistical Package for the Social Sciences (SPSS) Version 22 was used for running frequency analysis on the data set and multivariable regression modeling. The results showed that of 524 respondents, 382 (73%) had health insurance while 142 (27%) lacked insurance. Majority of insured respondents, 332 (87%), used preventive health services. However, the remaining 13% of respondents did not use preventive services because they were unfamiliar with the ACA provision of free access to preventive services for insured people. Regression analysis showed a high (91.04%) probability that, among the insured, the use of preventive health services depended on the person’s age, income, and education. For uninsured residents, the lack of health insurance was the key reason for non-use of preventive health services, while among the insured, lack of knowledge about the ACA benefit of free access contributed to non-use of preventive services. Expansion of Medicaid eligibility can increase insurance coverage rates among African Americans and other minority populations. Health promotion and awareness campaigns about the law’s benefits by local and state health departments can enhance the use of preventive services.